Abnormal Development of Haemaphysalis qinghaiensis (Acari: Ixodidae). Issue 1 (1st July 2016) - Ren, Qiaoyun; Chen, Ze; Luo, Jin; Liu, Guangyuan; Guan, Guiquan; Yin, Hong; Luo, Jianxun
Abstract: A single Haemaphysalis qinghaiensis specimen exhibiting abnormal morphology was collected from a tick laboratory colony. The tick had a heart-shaped body with partial twinning of the posterior region (with two anal orifices and two genital grooves). To the best of our knowledge, this is the first report of teratological changes in H. qinghaiensis . The abnormal morphological features are described herein.